Mahatma Gandhi Thoughts of Humanism And Nasionalism - Moses Adiman Tamba (International Journal on Social Science, Economics and Art, 2020)
Mahatma Gandhi was born in the social conditions that supported him to live in a strong moral environment. The notion of truth and non-violent resistance is a concept that comes to Gandhi’s mind to go grab a noble idea of his dreams. The deepening of religion is a key life that he got in his journey of life. Religion is a universal language, religion is about love and Gandhi have a noble desire to pass it on. Humanism is an understanding that Gandhi would like to practiced it in every resistance against things that are considered wrong and distorted. Satyagraha and Ahimsa are ideas and concepts that Gandhi used to explain the idea of struggle, which is considered by some to be not realistic with the development of increasingly intense armed conflict, but at the same time the answer to the criticism with concrete implementation which is driven by Gandhi in the struggle for India. Indian nationalism is built by Gandhi with propagate of Satyagraha and Ahimsa. Satyagraha is the goal and ahimsa is the way, the independence of India is the destination and abstinence or non-violence is the means to achieve independence. The practice of nonviolent resistance is the symbol of Gandhi’s award upon mankind that he thought it as a noble creature that must be treated well. Human ideas and actions is a different side of the body or the human body itself. That’s way Soekarno called Gandhi as a humanist-nationalist figure. The combination of nationalism and humanism maybe is a paradox in a theoretical debate. But in Gandhi’s mind a substance of truth above the theoretical debate. People may say that his idea is weird. But humanity cannot be explained by the theory, humanity is an action. Included when we fight against our enemy, because the enemy also a human that should we love too.